Effect of dolutegravir in combination with Nucleoside Reverse Transcriptase Inhibitors (NRTIs) on people living with HIV who have pre-existing NRTI mutations - Sörstedt, Erik; Carlander, Christina; Flamholc, Leo; Hejdeman, Bo; Svedhem, Veronica; Sönnerborg, Anders; Gisslén, Magnus; Yilmaz, Aylin (International journal of antimicrobial agents, 2018)
•First comparison between PI/r and dolutegravir in PLWH with baseline NRTI resistance.•A real-life setting involving intermediate- to high-level baseline NRTI resistance.•No new mutations were found among participants with treatment failure.•Dolutegravir is equally as efficient as traditional PI/r. Until the introduction of dolutegravir (DTG), people living with HIV (PLWH) who have developed nucleoside reverse transcriptase inhibitor (NRTI) mutations have had few other treatment options outside of regimens based on ritonavir-boosted protease inhibitors (PI/r). Here we report treatment results among PLWH in Sweden with pre-existing NRTI mutations on antiretroviral treatment (ART) with DTG and one to two NRTIs. All PLWH on ART with DTG and one to two NRTIs with pre-existing NRTI mutations were retrospectively identified from the National InfCare HIV database. As controls, PLWH on PI/r and one to two NRTIs, matched according to Genotypic Susceptibility Score and observation time, were included. Data were collected as long as the study population was on treatment with DTG; controls were monitored for the same interval. Outcome was classified as either treatment success or failure. In total, 244 participants (122 individuals treated with DTG and 122 individuals treated with PI/r) were included. Median observation time was 78 weeks (interquartile range 50–98 weeks) for participants on DTG and 75 weeks (50–101 weeks) for individuals on PI/r. Viral failure was detected in four individuals treated with DTG and three individuals treated with PI/r, resulting in similar success rates of 96.7% and 97.5%, respectively. No new mutations were found among participants with treatment failure. DTG in combination with one to two NRTIs was as efficient as PI/r in individuals with pre-existing NRTI mutations in this setting. It may be considered an alternative to PI/r-based ART even in the presence of NRTI resistance.